William Shakespeare and Thomas Mann: А Dispute about the Beauty and the Grace in the Historical Context of the Modern - Shalaghinov, Borys (Pitannâ lìteraturoznavstva, 2015)
The object of the given article is the further development of the moral potential of Nietzsche’s antibourgeois discourse. The actuality is also related with the aforesaid. The research method is the Marxism. Scientific novelty: a comparison of “Little Herr Friedemann” by Th. Mann and “Richard III” by W. Shakespeare in terms of F. Schiller’s teaching of “grace” is made for the first time. The article is a continuation of the author’s works cycle about the modernist project of the early romantics and its historical destiny. The essence of the interpretation: the heroine of the story is devoured by the excitement, not of Friedemann’s beauty (he has a hump), but of the liveliness of his intelligence and the ideas refinement; however, in a moment of the decisive declaration the force of life, which source is beauty, prevails. The thoughts excitement (grace) turns out to be fragile and unstable before the vitality, and consequently before the power of beauty; the life protects itself from an excessive refined anxiousness as from the element of the decline. The article states that Th. Mann follows conceptually F. Nietzsche. Greeks in “philosopher’s of life” conception were ready for the tragic collision with the fate, which was opposed by the power, not by the fine mobility of their own spirit. Nietzsche’s attention is paid to the images of the inner integrity and psychological solidity. In Nietzsche’s and Mann’s time Renaissance was interpreted as a symbiosis of beauty and strength, often cruel and pernicious, but fertile and buoyant. Although both authors treated rarely the images of Shakespeare, but jointly the “philosophy of life” was based on the Renaissance integrity, heroics and tragedy of human existence. The article is accentuated on the quintessential of the Nietzsche’s antibourgeois discourse: the integrity and the solidity of the personality is a condition of the tragic; gracefulness and elegance, emotional excitement (“grace”) lead to death even before the person managed to enter a competition with an inexorable necessity. Such is a common verdict of the philosopher and writer in the age of “decadence” to the bourgeois society, not capable to a tragic attitude.